Tourism Development in Banda Aceh City (A Study of Tourism Policy Implementation Based on Aceh Qanun Number 8 of 2013 concerning Tourism) - Said Mayzar Mulia; Agus Sholahuddin; Sri Hartini Jatmikowati (Budapest International Research and Critics University, 2020)
Tourism is a large economic sector and is very competitive at all levels - local, national, regional and international because of the benefits it brings and its contribution to the economy for urban development. Tourism development in each region, especially Banda Aceh City, should be well focused. Because the development in this sector challenges, movements and shifts will be very dynamic, so they must be continuously managed. This study uses a post positivist approach with data collection methods through literature, and in-depth interviews to find out Tourism Development in Banda Aceh City, the uniqueness of tourism in Banda Aceh City, as well as the factors that support and obstacles in implementing the Tourism policy in Banda Aceh City. The results of the study note that Tourism Development is a major work that must always be overseen planning and implementation that is formed with the development, infrastructure, promotion and marketing, structure (different organizations) and scale (international, national, local and sectoral).